Improving Cyclohexane Yield from Hydrogenation Benzene with a Modified Multistage Separation Design - Faiq, Nabihan Firas; Ghifari, Ahnaf Naufal; Hafizh, Dzakwan; Wafi, Muhammad Ariq; Failasofi, Muhammad Najih (UPT Laboratorium Terpadu, Universitas Diponegoro, 2025)
Cyclohexane is a compound that is widely used in various industrial applications as a chemical intermediate. Apart from that, this compound can also be used to produce solvents, insecticides and plasticizers. With the large use of cyclohexane, production with high efficiency in terms of yield is required. The aim of this research is to develop a process design for producing cyclohexane from benzene hydrogenation, with the aim of achieving high yield. This research uses an iterative simulation method to compare the basic process and a modified process for cyclohexane production. This process involves creating a simulation model using Aspen HYSYS and adjusting the process parameters until the desired results are achieved. The results of this research indicate that the cyclohexane produced in the modification process achieves a higher percentage of yield product. Based on the implemented process modification, there has been an increase in the yield of cyclohexane produced from 93.49% to 99.90%. Based on the results of this research, the modification process is proven to be able to increase yield and mass flow compared to the basic process system. Copyright © 2025 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).